2005
DOI: 10.1177/0013164404267285
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Scores on the Marlowe-Crowne Social Desirability Scale and the Balanced Inventory of Desirable Responding

Abstract: The Marlowe-Crowne Social Desirability Scale (MCSDS), the most commonly used social desirability bias (SDB) assessment, conceptualizes SDB as an individual’s need for approval. The Balanced Inventory of Desirable Responding (BIDR) measures SDB as two separate constructs: impression management and self-deception. Scores on SDB scales are commonly used to validate other measures although insufficiently validated themselves. This study used college students’ responses to the MCSDS and the BIDR to investigate thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(124 citation statements)
references
References 13 publications
3
115
0
6
Order By: Relevance
“…Besides the recoding of perceived CWB occurrence, a social desirability scale was also administered together with the survey. The current study employed the Fischer and Fick (1993) short version of the Marlowe-Crowne Social Desirability Scale (SDS), which is highly tested for its reliability in predicting socially conscious participants (Andrews & Meyer, 2003;Barger, 2002;Leite & Beretvas, 2005;Loo & Thorpe, 2000;Thompson & Phua, 2005). To check for social desirability issues, correlations were computed between the CWB-T factors and SDS.…”
Section: Issues Of Social Desirabilitymentioning
confidence: 99%
“…Besides the recoding of perceived CWB occurrence, a social desirability scale was also administered together with the survey. The current study employed the Fischer and Fick (1993) short version of the Marlowe-Crowne Social Desirability Scale (SDS), which is highly tested for its reliability in predicting socially conscious participants (Andrews & Meyer, 2003;Barger, 2002;Leite & Beretvas, 2005;Loo & Thorpe, 2000;Thompson & Phua, 2005). To check for social desirability issues, correlations were computed between the CWB-T factors and SDS.…”
Section: Issues Of Social Desirabilitymentioning
confidence: 99%
“…Nevertheless, rather than reflect these true thoughts or feelings (Grimm, 2010), attitudes, preferences or beliefs (Heerwig & McCabe, 2009), the need for approval (Leite & Beretvas, 2005) results in socially desirable responses (Pauls & Stemmler, 2003). The difference between the expression of socially responsible attitudes and actions is often referred to as the attitude-behaviour gap .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals whose responses to this scale are more socially desirable are thought to be more "conforming, cautious, and persuadable, and their behavior is more normatively anchored than persons who depict themselves less euphemistically" (Crowne & Marlowe, 1964, p. 189). The authors reported obtaining a Kuder-Richardson reliability coefficient of .88 and a testretest correlation of .89 (Leite & Beretvas, 2005).…”
Section: Marlowe-crowne Social Desirability Scalementioning
confidence: 97%